Perineal hernia mesh repair: a fixation with glue, sutures and tacks. How to do it . Issue 6 (2nd November 2019) - Hassan, L.; Beunis, A.; Ruppert, M.; Dhooghe, V.; Van den Broeck, S.; Hubens, G.; Komen, N.
Abstract: Introduction: Many different approaches for the repair of a perineal hernia (PH) after abdomino-perineal rectum amputation (APR) have been described throughout the years. Literature shows us that the use of a mesh had the best results with relatively low rates of recurrence compared to primary suture. Yet there is still no consensus on the best technique for fixation of the mesh in the perineal cavity. Methods: We want to introduce an addition to the surgical repair technique, using laparoscopic glue to ensure a solid fixation of the mesh. This is to prevent small bowel from sliding into the perineal area due to the high abdominal pressure when standing and to avoid the difficulties and risks of laparoscopical suturing in this area. Results : This use of glue for fixation of the mesh has been successful in the three cases described, with no recurrence after one-year follow-up. Conclusion : A recurrent PH can be prevented by a solid fixation of the mesh using the technique of a glued mesh repair. This technique shows to be easy, fast and without recurrence.